Vegetative propagation of Pelargonium sidoides D.C. (Rabassam) using leaf-bud cuttings - Du Toit, Elsie Sophia (University of Pretoria, 2025)
Dissertation (MScAgric (Horticulture))--University of Pretoria, 2019.